Go or no-go? Developmental improvements in the efficiency of response inhibition in mid-childhood. - Cragg, L; Nation, K (2008)
This experiment used a modified go/no-go paradigm to investigate the processes by which response inhibition becomes more efficient during mid-childhood. The novel task, which measured trials on which a response was initiated but not completed, was sensitive to developmental changes in response inhibition. The effect of inducing time pressure by narrowing allowable response time was also examined. While increasing time pressure did not reduce the inhibitory demands of the task for either age group, older children (aged 9 to 11 years) were able to inhibit their responses at an earlier stage of movement than younger children (aged 5 to 7 years). This shows that as children get older they become more efficient at controlling their behaviour which drives developmental improvements in response inhibition.